DECOHERENCE-FREE SUBSPACES FOR OPEN QUANTUM RANDOM WALKS ON GRAPHS - Agredo, J. (Publicaciones académicas Ltd., 2016)
We study decoherence-free subspaces in a type of Quantum Markov Semigroups called continuous-time open quantum random walks on graphs. We measure the temporary changes of quantum correlations using geometric quantum discord with bures distance under some assumptions about the semigroup. In particular, we characterize the decay of correlations to zero, showing that turns out to be closely related with the structure of decoherence-free subspace.

Estudiamos subespacios libres de decoherencia en un tipo de semigrupos cuánticos de Markov denominados paseos aleatorios cuánticos abiertos de tiempo continuo sobre grafos. Medimos los cambios temporales de las correlaciones cuánticas utilizando la discordancia cuántica geométrica con distancia de bures bajo algunas suposiciones sobre el semigrupo. En particular, caracterizamos el decaimiento de las correlaciones a cero, mostrando que resulta estar estrechamente relacionado con la estructura del subespacio libre de decoherencia.
Keywords: Cuantización geométrica; Correlaciones cuánticas; Quantum Markov semigroup; Geometric quantum discord; Bures distance; Decoherence-free subspaces; Semigrupo cuántico de Markov; Discordancia cuántica geométrica; Distancia de Bures; Subespacios libres de decoherencia